Insights into epigenetic regulation of cyp19a via comparative analysis using the scombrid chub mackerel as model - Galotta, Mariel; Dam, Anh Tuan; Eto, Yuhei; Toyoda, Atsushi; Itoh, Takehiko; Mohapatra, Sipra; Ogino, Yukiko; Saitou, Marie; Matsuyama, Michiya; Chakraborty, Tapas; Ohta, Kohei (Frontiers in Marine Science, 2024)
Sexual development and reproduction are largely linked to epigenetic changes in many fish species. However, understanding of epigenetic regulation in scombrid species, such as tunas and mackerels, is limited. This study investigates DNA methylation's impact on cyp19a expression, crucial for estrogen synthesis, focusing on chub mackerel. Given the commercial significance of scombrids and susceptibility of marine fish to environmental changes, elucidating epigenetic mechanisms, particularly in the context of global warming, becomes imperative. We aimed to generalize observations from chub mackerel to other scombrids. Additionally, we studied DNA methylation patterns across fish with different sexual systems to understand aromatase regulation's phenotypic plasticity. Our in silico analysis revealed highly conserved promoter sequences within scombrids, sharing TFBS like Foxl2, FOS::JUN, ESRR, and Sox3, while CpG content varies. This indicates a conserved regulatory network controlling gene expression. We found sexual dimorphism in DNA methylation, with males hypermethylated and aromatase expression downregulated. Despite similar dnmt1 expression, tet1, tet2, and tet3 were higher expressed in females, suggesting that the observed DNA methylation patterns are maintained through active demethylation rather than differential methylation. Gonochoristic Japanese anchovy and protogynous bamboo leaf wrasse displayed similar trends, but species-specific methylation patterns highlight DNA methylation's complex role in gonadal changes. In vitro assays confirmed methylation's regulatory role and identified an SF-1 binding site relevant for promoter activation in chub mackerel. Another studied SF-1 site, present in both chub mackerel and bamboo leaf wrasse, showed regulatory effects, indicating potential similar regulatory mechanisms for cyp19a expression. Overall, our findings suggest that while global methylation affects cyp19a transcription, the variation in CpG density and location could be introducing nuances in its epigenetic regulation. This study contributes to our understanding of the cyp19a regulation in fish gonad maturation.